TUBULAR DISORDERS WITH RICKETS-LIKE SYNDROME - N.N. Kartamysheva; T.V. Vashurina; A.M. Mazo; A.B. Sugak; E.N. Tsygina; M.I. Bakanov; A.N. Tsygin (Педиатрическая фармакология)
Often under the guise of «ordinary» Rickets are more severe kidney diseases, developing as a result of inherited or acquired, primary or secondary defects in the renal tubules. Incorrect diagnosis leads to an inadequate therapy, rapid progression of disease and renal failure. The article describes the main approaches to the diagnosis and treatment of disorders of tubular rachitis similar syndrome, presents a number of clinical cases in author's practice.Key words: tubulopathy, acidosis, electrolyte disorders, rickets, rickets-like syndrome, diagnostics, treatment, children.